Financial Management Based On Analysis Of Financial Accounting Standards For Entities Without Public Accountability (SAKETAP): Empirical Study on Kafanaa Mie and Chicken Restaurant Customers - Lilik Ismawati; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (International Journal of Economics and Management Research, 2023)
This research aims to analyze the financial management of the Kafanaa Mie and Chicken restaurant based on the analysis of Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). The research method used is an empirical study with data collection techniques through interviews and observation. Unfortunately, the research results show that Kafanaa Mie and Chicken still has not carried out financial management of cash flow and has not prepared financial reports in accordance with SAK ETAP. This research provides recommendations for better financial management and preparing financial reports in accordance with SAK ETAP to improve restaurant financial performance.